Utility of the acute phase inflammatory risk index as a predictor of severity in preeclampsia - Rios-Mino, Diana L. (2023)
Objective: determine the usefulness of the acute phase inflammatory risk index as a predictor of severity in preeclampsia. Material and method: an analytical observational study of diagnostic tests was carried out, in which 152 pregnant women in the third trimester of pregnancy attended by the Gynecology – Obstetrics service of the Belén Hospital of Trujillo were included, divided into two groups: 76 pregnant women with a diagnosis of preeclampsia with and without severity criteria. In these groups, the following parameters were evaluated: neutrophil/lymphocyte ratio (INL), platelet/lymphocyte ratio (PLI), hemoconcentration, hematocrit/albumin ratio (HAI), mean platelet volume (MPV), erythrocyte distribution width (RDW)  and the acute phase inflammatory risk index. Results: in the laboratory characteristics, the neutrophil lymphocyte index (NLR), platelet lymphocyte index (LPI), hemoconcentration, mean platelet volume (MPV) and erythrocyte distribution width (RDW), by themselves, did not have statistical significance. However, the albumin hematocrit index >12 alone did obtain statistical significance (p=0.001). Likewise, the inflammatory risk index as a predictor of severity was associated with severity in preeclampsia. Through the ROC curves, it was found that the best cut-off point was 2.5, sensitivity 68.4%, specificity 50.0%, positive predictive value 57.8% and negative predictive value 61.3%. Conclusion:  the Acute Phase Inflammatory Risk Index > 2.5 should be considered a useful factor for predicting severity in preeclampsia.